On the nature of civilization in the Grand Duchy of Lithuania - Bumblauskas, Alfredas (Lietuvos istorijos studijos, 1996)
The article by the medievalist historian presents a critical review of the reports on the nature of civilization in the Grand Duchy of Lithuania in Polish, Russian, German, and Lithuanian historiography based on the definition of civilization by the Polish theorist of history, Feliks Koneczny ("Civilization is a method of arranging communal life"), and proves that this civilization was neither Western-Latin nor Eastern-Byzantine, but, rather, quite an independent one, with its own necessary minimum of European values.